Capture and immobilization of gaseous ruthenium tetroxide RuO4 in the UiO-66-NH2 metal–organic framework. Issue 42 (7th October 2022) - Leloire, Maëva; Nerisson, Philippe; Pourpoint, Frédérique; Huvé, Marielle; Paul, Jean-François; Cantrel, Laurent; Loiseau, Thierry; Volkringer, Christophe
Abstract : UiO-66-NH2 is a highly efficient porous material for the capture and immobilization of gaseous RuO4, a highly toxic molecule produced during a nuclear accident. Abstract : 106 Ru is a radioactive isotope usually generated by the nuclear industry within power plant reactors. During a nuclear accident, 106 Ru reacts with oxygen, leading to the production of highly volatile ruthenium tetroxide RuO4 . The combination of volatility and radioactivity makes 106 RuO4, one of the most radiotoxic species and justifies the development of a specific setup for its capture and immobilization. In this study, we report for the first time the capture and immobilization of gaseous RuO4 within a porous metal–organic framework (UiO-66-NH2 ). We used specific installation for the production of gaseous RuO4 as well as for the quantification of this gas trapped within the filtering medium. We proved that UiO-66-NH2 has remarkable affinity for RuO4 capture, as this MOF exhibited the worldwide highest RuO4 decontamination factor (DF of 5745), hundreds of times higher than the DF values of sorbents daily used by the nuclear industry (zeolites or activated charcoal). The efficiency of UiO-66-NH2 can be explained by its pore diameters well adapted to the capture and immobilization of RuO4 as well as its conversion into stable RuO2 within the pores. This conversion corresponds to the reactivity of RuO4 with the MOF organic sub-network, leading to the oxidation of terephthalate ligands. As proved by powder X-ray diffraction and NMR techniques, these modifications did not decompose the MOF structure.